1993
DOI: 10.1073/pnas.90.16.7533
|View full text |Cite
|
Sign up to set email alerts
|

Fetal liver kinase 1 is a receptor for vascular endothelial growth factor and is selectively expressed in vascular endothelium.

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
354
2
10

Year Published

1995
1995
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 669 publications
(380 citation statements)
references
References 26 publications
14
354
2
10
Order By: Relevance
“…We therefore refer to the murine flt-1 receptor as VEGFRlLIflt-1. The apparent Kd for VEGF binding to murine VEGFRlAlt-1, as calculated by using a nonlinear regression curve, was 90 pM and, as determined by Scatchard analysis, 114 pM, being somewhat higher than recently described for human VEGFRlAlt-1 (Quinn et al, 19931, but considerably lower than the reported K, for VEGF binding to murine VEGFRZLI flk-1 (approximately 600 pM; Millauer et al, 1993;Quinn et al, 1993).…”
Section: Isolation and Characterization Of A Mouse Flt-1 Cdnamentioning
confidence: 54%
“…We therefore refer to the murine flt-1 receptor as VEGFRlLIflt-1. The apparent Kd for VEGF binding to murine VEGFRlAlt-1, as calculated by using a nonlinear regression curve, was 90 pM and, as determined by Scatchard analysis, 114 pM, being somewhat higher than recently described for human VEGFRlAlt-1 (Quinn et al, 19931, but considerably lower than the reported K, for VEGF binding to murine VEGFRZLI flk-1 (approximately 600 pM; Millauer et al, 1993;Quinn et al, 1993).…”
Section: Isolation and Characterization Of A Mouse Flt-1 Cdnamentioning
confidence: 54%
“…8 Another high-affinity VEGFR, Flt-1, binds VEGF about 10 times stronger than KDR, however Flt-1 activation does not significantly stimulate angiogenesis. 9,10 Both receptors, Flt-1 and KDR, have similar structure with extracellular regions consisting of seven domains, 1-7. 10,11 There exists another naturally occurring soluble form of Flt-1 (sFlt-1) that contains only the extracellular domains and has the same VEGF-binding affinity as full-length Flt-1.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Both receptors, Flt-1 and KDR, have similar structure with extracellular regions consisting of seven domains, 1-7. 10,11 There exists another naturally occurring soluble form of Flt-1 (sFlt-1) that contains only the extracellular domains and has the same VEGF-binding affinity as full-length Flt-1. 11,12 The VEGF-binding function of Flt-1 has been mapped to the second domain.…”
Section: Introductionmentioning
confidence: 99%
“…VEGF binds to two receptor-type tyrosine kinases, Flt-1 (VEGF receptor-1) (Shibuya et al, 1990;de Vries et al, 1992) and KDR/ Flk-1 (VEGF receptor-2) (Quinn et al, 1993), and to membrane protein neuropilin-1, which does not contain a tyrosine kinase domain (Soker et al, 1998). Flt-1 and KDR/Flk-1 have seven immunoglobulin-like repeats in the extracellular domain, a single transmembrane region, and a tyrosine kinase domain in the intracellular domain that is interrupted by a kinaseinsert domain.…”
Section: Introductionmentioning
confidence: 99%